Recent Development in Therapeutic Cardiac Patches - Mei, Xuan; Cheng, Ke (Frontiers in Cardiovascular Medicine, 2020)
For the past decades, heart diseases remain the leading cause of death worldwide. In adult mammalian heart, damaged cardiomyocytes will be replaced by non-contractile fibrotic scar tissues due to the poor regenerative ability of heart, causing heart failure subsequently. The development of tissue engineering has launched a new medical innovation for heart regeneration. As one of the most outstanding technology, cardiac patches hold great potential to restore cardiac function clinically. Consisted of two components: therapeutic ingredients and substrate scaffolds, the fabrication of cardiac patches requires both advanced bioactive molecules and biomaterials. In this review, we will present the most state-of-the-art cardiac patches and analysis their compositional details. The therapeutic ingredients will be discussed from cell sources to bioactive molecules. In the meanwhile, the recent advances to obtain scaffold biomaterials will be highlighted, including synthetic and natural materials. In addition, we have focused on the challenges and potential strategies to fabricate clinically applicable cardiac patches.